Ar-Rahnu Energy Cooperative (AREC): A Community-Based Microfinance Model for Green Development in Indigenous Aceh - Mustaqilla, Nazhira (Indonesian Journal of Energy, 2026)
The tradition of gold dowries in Aceh has resulted in women owning significant amounts of gold, yet these assets often remain unproductive and are merely stored as passive savings. This study explores the Gala or Ar-Rahnu or Jeulamee tradition and proposes a community-based financing model that optimizes unproductive gold as capital for Energy Independent Villages in Aceh. The novelty of this research lies in introducing Jeulamee as an alternative financing mechanism for renewable energy. This approach has not been previously examined while designing a closed-loop ecosystem to ensure sustainable energy production at the community level. Employing a mixed methods approach, including Location Quotient, Dynamic Location Quotient, Shift Share, and Input-Output analysis, the study identifies strategic sectors for sustainable energy development and formulates the Ar-Rahnu Energy Cooperative concept. By integrating Islamic microfinance, indigenous cultural practices, and blockchain-based gold tokenization, this research contributes to the literature on green financing while offering practical implications for women’s economic empowerment, improved access to clean energy, and the advancement of inclusive and sustainable energy transitions in indigenous communities.